Legal Analysis Of Giving Remission To Fostered Citizens Of Criminal Acts In Narcotics In The Narcotics Special Class IIa Gintung Cirebon - Suhada Suhada; Aryani Witasari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The problems of this study are: 1) How can the application of remissions the inmates of narcotics cases in the Penitentiary (Prison) Narcoticts Class IIA Gintung Cirebon? 2) Are the obstacles in granting remission to the prisoners in the prisons of narcotics cases Narcotics Class IIA Gintung Cirebon?The method used is a sociological juridical approach. Specifications research used in this research is descriptive analysis. The sources and types of data in this study are primary data and secondary data.Based on the results of this study concluded that Application of remissions the inmates of narcotics cases in the Penitentiary (Prison) Narcoticts Class IIA Gintung Cirebon tightened after the enactment Government Regulation No. 99 Of 2012 and the Regulation of the Minister of Law and Human Rights No. 3 of 2018. Constraints in granting remission to the prisoners in the prisons of narcotics cases Narcotics Class IIA Gintung Cirebon because in addition to the provisions stipulated by Government Regulation No. 99 Of 2012 and the Regulation of the Minister of Law and Human Rights No. 3 of 2018, also the following provisions: a) Punishable with a penalty of less than 6 months; b) Disciplinary penalties and violations are listed at the register book prisons or detention order within the time period taken into account in granting remission; c) Leave ahead of undergoing free; d) Sentenced to imprisonment substitute fines.Keywords: Legal Analysis; Remission; Citizens Patronage of Corrections; Crime; Narcotics